2015
DOI: 10.1080/19440049.2015.1084652
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-anthesis rainfall, fungicide and harvesting time on the concentration of deoxynivalenol and zearalenone in wheat

Abstract: Field experiments were conducted to identify the impact of post-anthesis rainfall on the concentration of deoxynivalenol (DON) and zearalenone (ZON) in harvested wheat grain. Winter wheat plots were inoculated with Fusarium graminearum at stem extension (GS31) and prothioconazole was applied at mid-anthesis (GS65) to split plots and plots were subsequently mist irrigated for 5 days. Plots were either covered by polytunnels, irrigated by sprinklers or left as non-irrigated uncovered control plots after medium-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
3
27
2
Order By: Relevance
“…All analysis showed significant interactions (P<0.05). Prior to the treatments the DON concentration in mill fractions were as reported previously for wheat harvested in the UK in 2005 (Kharbikar, Dickin, & Edwards, 2015) with lower DON concentrations in the SRF and more in the bran and offal fractions ( Figure 2a). There was little change in the concentration of DON in cleaned grain, SRF and bran but a significant reduction (40%) in DON in the offal fraction occurred after repeated conditioning.…”
Section: Laboratory Water Experimentssupporting
confidence: 76%
“…All analysis showed significant interactions (P<0.05). Prior to the treatments the DON concentration in mill fractions were as reported previously for wheat harvested in the UK in 2005 (Kharbikar, Dickin, & Edwards, 2015) with lower DON concentrations in the SRF and more in the bran and offal fractions ( Figure 2a). There was little change in the concentration of DON in cleaned grain, SRF and bran but a significant reduction (40%) in DON in the offal fraction occurred after repeated conditioning.…”
Section: Laboratory Water Experimentssupporting
confidence: 76%
“…We detected an increased DON content in oat grains harvested from fields with cool and moist weather during this period. The importance of moisture post-flowering has also been reported alone (Cowger et al 2009;Andersen et al 2015;Kharbikar et al 2015) and in combination with warm weather (Franz et al 2009). No association was detected between the DON accumulation and rain during late milk and dough development in our study, although a positive association was detected between DON and precipitation during milk development.…”
Section: Association Between Don Content and Weather Conditions At DIcontrasting
confidence: 55%
“…In a previous article, we found a clear relationship between higher precipitation and high levels of DON and ZEN56. Some recent publications have suggested that environmental conditions, especially moisture in the form of rainfall or relative humidity, are associated with higher DON and ZEN accumulation505758.…”
Section: Discussionmentioning
confidence: 57%